2004
DOI: 10.1016/j.visres.2003.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Letter-recognition and reading speed in peripheral vision benefit from perceptual learning

Abstract: Visual-span profiles are plots of letter-recognition accuracy as a function of letter position left or right of the midline. Previously, we have shown that contraction of these profiles in peripheral vision can account for slow reading speed in peripheral vision. In this study, we asked two questions: (1) can we modify visual-span profiles through training on letter-recognition, and if so, (2) are these changes accompanied by changes in reading speed? Eighteen normally sighted observers were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
254
14
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(308 citation statements)
references
References 29 publications
35
254
14
5
Order By: Relevance
“…† It is possible that the impressive improvement in reading speed in Nilsson et al's study might have been due, at least in part, to training in peripheral reading per se, rather than to the advantage of the TRL location. Chung et al (2004) found a significant but smaller increase in peripheral reading speed among normally sighted participants after training on a letterrecognition task in peripheral vision. Their participants were trained 2 h per day for 4 days, one group at 10 deg above fixation and a second group 10 deg below fixation.…”
Section: Function-driven Explanation Of Prlmentioning
confidence: 77%
“…† It is possible that the impressive improvement in reading speed in Nilsson et al's study might have been due, at least in part, to training in peripheral reading per se, rather than to the advantage of the TRL location. Chung et al (2004) found a significant but smaller increase in peripheral reading speed among normally sighted participants after training on a letterrecognition task in peripheral vision. Their participants were trained 2 h per day for 4 days, one group at 10 deg above fixation and a second group 10 deg below fixation.…”
Section: Function-driven Explanation Of Prlmentioning
confidence: 77%
“…17 The 2-fold aim of the present study was to compare baseline reading performance of those children with the age-matched controls with normal vision, and to assess training-induced changes in their reading performance. Our participant group of children with IN consisted of children with idiopathic IN and children with albinism accompanied by IN. Previous studies have demonstrated that reading performance can be improved by perceptual learning, [18][19][20] which refers to a long-term performance increase resulting from perceptual experience. 21 The reading measure that is improved by perceptual learning depends on the paradigm used.…”
mentioning
confidence: 99%
“…Left -to-right-reading adults should be bett er at identifying words within the central or right-to-central part of their visual fi eld because that is where they have adapted to visualize words while learning to read (Chung, Legge, & Cheung, 2004). Yet, there is no clear left ward asymmetry of the OVP eff ect in languages read from right to left , such as Arabic or Hebrew (Farid & Grainger, 1996;Nazir et al, 2004).…”
Section: Introductionmentioning
confidence: 99%